IMPLEMENTASI PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) TERINTEGRASI KONSEP UNDERSTANDING BY DESIGN (UBD) UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SMA PADA PEMBELAJARAN BIOLOGI - Ni Nyoman Serma Adi; Dewa Nyoman Oka; I Ketut Surata (Widyadari, 2024)
Teaching at the right level (Tarl) is a student-centered learning approach where students are grouped into groups with certain cognitive levels. Meanwhile, Understanding by Design (Ubd) is a reverse learning design or backward design where the process consists of determining objectives, then assessing and compiling learning activities which, if integrated, will be able to achieve optimal learning objectives and increase learning motivation. This research aims to determine whether the implementation of teaching at the right level (Tarl) integrated with the concept of Understanding by design (Ubd) can increase students’ learning motivation at Surya Wisata Kediri Tabanan Senior High School. This type of research is classroom action research (PTK), using a cycle design from Kemmis & Mc Taggard. The location of this research is at Surya Wisata Kediri High School in class X MIPA 1 with research subjects of 32 students. Based on the research, the results obtained are that the implementation of the Teaching at the Right Level (TaRL) approach integrated with the Understanding by Design (UBD) concept can increase students’ learning motivation, where in the pre-cycle the percentage of students was in the low category, in the first cycle the percentage was 24.21%. Student motivation increased to 59.24% in the medium category and in cycle II it increased to 80.56% in the high category. So it can be concluded that the implementation of the Teaching at the Right Level (TaRL) approach integrated with the concept of Understanding by Design (UbD) can increase high school students’ learning motivation in learning biology.